Penegakan Hukum Terhadap Pelaku Pelanggaran Membuang Sampah Tidak Sesuai Jadwal Berdasarkan Perda Kabupaten Karangasem Nomor 20 Tahun 2012 - I Kadek Arya Wiryawan; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Environmental protection and management is a systematic and integrated effort carried out to preserve environmental functions and prevent environmental pollution and/or damage which includes planning, utilization, control, maintenance, supervision and law enforcement. The formulation of the problem in this study are: How is law enforcement against perpetrators of violations of waste disposal not according to schedule based on Regional Regulation of Karangasem Regency Number 20 of 2012 concerning Waste Management and How are the obstacles and efforts made by the Government of Karangasem Regency against perpetrators of violations of inappropriate waste disposal timetable. The results of this study include: Law enforcement against perpetrators of violations of waste disposal not according to schedule based on Regional Regulation of Karangasem Regency Number 20 of 2012 concerning Waste Management, among others: Starting with the findings of the task force in the field of violations of disposing of waste not according to schedule. Violators of disposing of waste not according to schedule are subject to administrative sanctions in the form of: making a statement that they will not repeat their actions, being given warnings and warnings, being subject to forced fees, up to a recommendation to revoke the cancellation of their activities and business permits. Karangasem against perpetrators of violations of waste disposal that are not according to schedule, the obstacles faced include: The condition of infrastructure is still inadequate, causing vehicle operations to be less effective. Preventive efforts are carried out by conducting socialization, making a schedule for garbage collection. The repressive efforts are carried out, namely if there are people who violate the provisions, such as throwing garbage out of place, they will be subject to administrative sanctions by making a statement that they will not repeat their actions again.